Teacher Efficacy and the Effects of Coaching on Student Achievement - Ross, John (Canadian Journal of Education/Revue canadienne de l’éducation, 1992)
This research considers relationships between student achievement (knowledge and cognitive skill), teacher efficacy (Gibson & Dembo, 1984), and interactions with assigned coaches (self-report measures) in a sample of 18 grade 7 and 8 history teachers in 36 classes implementing a specific innovation with the help of 6 coaches. Student achievement was higher in classrooms of teachers who had more contact with their coaches and in classrooms of teachers with greater confidence in the effectiveness of education. Teachers who relied on school administrators reported less involvement with their coaches and these teachers obtained lower student achievement. There was no interaction between efficacy and coaching, possibly because there was virtually no peer observation. Cette recherche porte sur les relations entre le rendement scolaire (connaissance et aptitude cognitive), l’efficacité des enseignants (Gibson et Dembo, 1984) et les interactions avec des aidants (mesures d’auto-évaluation) dans un échantillon de 18 enseignants d’histoire dans 36 classes de 7e et 8e année où était implantée une innovation avec l’intervention de six aidants. Le rendement scolaire a été supérieur dans les classes des enseignants qui avaient plus de contacts avec leurs aidants et dans celles des enseignants ayant une plus grande confiance dans l’efficacité de l’éducation. Les enseignants qui comptaient sur les administrateurs scolaires ont fait état de contacts moins nombreux avec leurs aidants et ont obte- nu un rendement scolaire inférieur. Il n’y avait aucune interaction entre l’effica- cité et l’encadrement des aidants, peut-être parce qu’il n’y avait presque aucune observation mutuelle.